Canadian Stroke Best Practice Recommendations: Rehabilitation, Recovery, and Community Participation following Stroke. Part One: Rehabilitation and Recovery Following Stroke; 6th Edition Update 2019. Issue 7 (October 2020) - Teasell, Robert; Salbach, Nancy M; Foley, Norine; Mountain, Anita; Cameron, Jill I; Jong, Andrea de; Acerra, Nicole E; Bastasi, Diana; Carter, Sherri L; Fung, Joyce; Halabi, Mary-Lou; Iruthayarajah, Jerome; et al.
The sixth update of the Canadian Stroke Best Practice Recommendations: Rehabilitation, Recovery, and Reintegration following Stroke. Part one: Rehabilitation and Recovery Following Stroke is a comprehensive set of evidence-based guidelines addressing issues surrounding impairments, activity limitations, and participation restrictions following stroke. Rehabilitation is a critical component of recovery, essential for helping patients to regain lost skills, relearn tasks, and regain independence. Following a stroke, many people typically require rehabilitation for persisting deficits related to hemiparesis, upper-limb dysfunction, pain, impaired balance, swallowing, and vision, neglect, and limitations with mobility, activities of daily living, and communication. This module addresses interventions related to these issues as well as the structure in which they are provided, since rehabilitation can be provided on an inpatient, outpatient, or community basis. These guidelines also recognize that rehabilitation needs of people with stroke may change over time and therefore intermittent reassessment is important. Recommendations are appropriate for use by all healthcare providers and system planners who organize and provide care to patients following stroke across a broad range of settings. Unlike the previous set of recommendations, in which pediatric stroke was included, this set of recommendations includes primarily adult rehabilitation, recognizing many of these therapies may be applicable in children. Recommendations related to community reintegration, which were previously included within this rehabilitation module, can now be found in the companion module, Rehabilitation, Recovery, and Community Participation following Stroke. Part Two: Transitions and Community Participation Following Stroke .